Предмет: Алгебра,
автор: filitsiyadekarlo
Вычислите f'(0)+f'(-1), если f(х) = 4х2 + 7х – 3.
Ответы
Автор ответа:
0
F ( x ) = 4x^2 + 7x - 3
F ' ( x ) = 8x + 7
F ' ( 0 ) = 7
F ' ( - 1 ) = - 8 + 7 = - 1
F ' ( 0 ) + F ' ( - 1 ) = 7 - 1 = 6
Ответ 6
F ' ( x ) = 8x + 7
F ' ( 0 ) = 7
F ' ( - 1 ) = - 8 + 7 = - 1
F ' ( 0 ) + F ' ( - 1 ) = 7 - 1 = 6
Ответ 6
Автор ответа:
0
в первой строке решения ^ что это означает
Автор ответа:
0
Степень числа
Автор ответа:
0
4х2 = 4х^2 ( одно и тоже )
Автор ответа:
0
спасибо
Похожие вопросы
Предмет: Английский язык,
автор: vasia7654
Предмет: Математика,
автор: levongarsayn36
Предмет: Геометрия,
автор: Mafia2194
Предмет: Обществознание,
автор: sonyxp2p